Altered Tryptophan Metabolism as a Paradigm for Good and Bad Aspects of Immune Privilege in Chronic Inflammatory Diseases - Li, Lingqian; Huang, Lei; Lemos, Henrique; Mautino, Mario; Mellor, Andrew L. (Frontiers in Immunology, 2012)
The term ‘immune privilege’ was coined to describe weak immunogenicity (hypo-immunity) that manifests in some transplant settings. We extended this concept to encompass hypo-immunity that manifests at local sites of inflammation relevant to clinical diseases. Here, we focus on emerging evidence that enhanced tryptophan catabolism is a key metabolic process that promotes and sustains induced immune privilege, and discuss the implications for exploiting this knowledge to improve treatments for hypo-immune and hyper-immune syndromes using strategies to manipulate tryptophan metabolism.